Analisis Dampak Penerapan Asas Cabotage Terhadap Peningkatan Daya Saing Lembaga Klasifikasi Nasional Studi Kasus Wilayah Kepulauan Riau - Malisan, Johny (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
Commitment to implement cabotage principle has been initiated bij Presidential Instmction No. 5 /2005 on the Empowennent of Domestic Shipping Industnj and strengthened biJ I.mu No. 17 of2008on Shipping. 171is gives a positive impact to increase activities of domestic ship classification. Itsgrawth is also supported biJ a number of foreign classifications which also operate in Indonesia.177e implementation of cabotage principle is not just related to crews and cargoes on board, but also tothe obligation of vessel class to national classification. Activities of ship classifications are to registerand collect physical and tedmical of ship, ownership and flag entitle to fly in order to promote safehJand seaworthiness aspects. Currently national classification has registered abaut 90 % of tl7e totalIndonesian flag ships. But t11e problem that still appeared is less confident anwng ship-owners andinsurance to tl7e result of national classification.As a consequence there is no equalihJ with other similar international classification bodies. Therefore,analysis and evaluation of the impact occurred for national ship classification in line with cabotageprinciple stated in Presidential Instruction No. 5 / 2005. Selected location of SUrvetj is Riau Islands onthe consideration that tl7e number of shipiJards (national and foreign) operating there are more thanotl7er region and also number of ship calls tend to increase.